Pediatric Ophthalmology Fellowship Survey: Fellows Selection Criteria for Training Programs - Singh, Jasleen K.; Lovelace, Kimberly; Patnaik, Jennifer L.; Enzenauer, Robert (Journal of Academic Ophthalmology, 2018)
Purpose This article investigates the characteristics that trainees look for in a pediatric ophthalmology fellowship program.Methods A 14-question anonymous survey was created and sent out via the United States Postal Service to all physicians of American Association of Pediatric Ophthalmology and Strabismus. The survey addressed demographics, the interview process, and the qualities of fellowship training programs that were important factors in ranking fellowship training programs. A Likert scale was used to rate different qualities (1: not important, 9: very important) and summary statistics were reported as overall means and standard deviations.Results In total, 1,061 were mailed out with 413 returned amounting to a 38.9% response rate. The qualities with the highest mean were diversity of surgical procedures, volume of procedures/surgeries, reputation of the fellowship director, advice from mentor, emphasis on type of surgery performed, program association with an academic institution, and national reputation of program. The characteristics that ranked the lowest were presence of a Veteran's Administration hospital and presence of a county hospital. Females rated proximity to family significantly higher than males. Among responders who ranked volume of procedures/surgeries as very important, strabismus surgery was the most important.Conclusion Pediatric ophthalmologists chose fellowship training programs based on the diversity and surgical volume of procedures and the reputation of the program director.
Keywords: pediatric ophthalmology; fellowship; survey; program